FARMER'S RESPONSE TO UPSUS PAJALES PROGRAMS IN ORDER TO INCREASE CORN PRODUCTION IN JEMBER DISTRICT: FARMER'S RESPONSE TO UPSUS PAJALES PROGRAMS IN ORDER TO INCREASE CORN PRODUCTION IN JEMBER DISTRICT - Nurul Awaliatul Istikhomah; Ebban Bagus Kuntadi (Tanjungpura International Journal on Dynamics Economics, Social Sciences and Agribusiness, 2020)
Abstract: Special effort (UPSUS) program of sustainable self-sufficiency is one of the government efforts in manifesting food security. UPSUS of food self-sufficiency is focused on three types of main food commodities that are rice, corn, and soybean (PAJALE). UPSUS PAJALE program aims to increase the production of rice, corn, and soybean so that it reaches sustainable food self-sufficiency. Jember Regency is one of the corn centrals running UPSUS PAJALE program. Ambulu Sub District is one of the areas running UPSUS PAJALE program for new planting areas extension (PATB) of corn in Jember Regency. PATB program of corn leads to new planting extension. The PATB activity of corn supports the farmers in cultivating corn because there is facility assistance in the form of corn seed. The activity brings up farmers response in conducting corn farming activity. Farmers response can be knowledge, attitude, and behavior of farmers taking an important effect on the PATB activity implementation of corn. This research aims to (1) find out the farmers respond on UPSUS PAJALE program, and (2) find out factors affecting the farmers response on UPSUS PAJALE program. The research area determination with the purposive method was Ambulu Sub District Jember Regency. Sample determination method was by simple random sampling with total samples as 63 farmer respondents. Data collection method was by observation, interview, and documentation. The tools of analysis used proportion test of Z-statistic and multiple linear regression analysis. The results of the research showed that (1) Farmers response on PATB activity of corn on UPSUS PAJALE program to increase corn production in Ambulu Sub District Jember Regency included in high response category. (2) Factors affecting the farmers response significantly on PATB activity of corn on UPSUS PAJALE program in Ambulu Sub District Jember Regency are price, visit frequency of field extension officer (PPL) and education. Factors not affecting significantly on the farmers response on PATB activity of corn on UPSUS PAJALE program in Ambulu Sub District Jember Regency are land area, age, farm management, and land ownership. Keywords: PATB of corn, UPSUS PAJALE Program, Response